2011
DOI: 10.1007/s11548-011-0624-y
|View full text |Cite
|
Sign up to set email alerts
|

Visualization support for the planning of hepatic needle placement

Abstract: The proposed visualization approach can both accelerate the access path planning for radiofrequency ablation in the liver and facilitate the differentiation between safer and less safe paths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…3D visualisation treatment planning can be used in the quantitative calculation of tumour volume and the distance between the tumour and surrounding vital structures, as well as accurate simulation of 3D thermal fields and planning of the puncture pathway. 3D visualisation preoperative planning has been applied in liver thermal ablation [18,24,25]. On the basis of the characteristics and clinical application requirements of US-guided PMWA for larger RCC, we combined 3D visualisation treatment planning, US-guided PMWA, artificial ascites and a thermal monitoring system for larger RCC.…”
Section: Discussionmentioning
confidence: 99%
“…3D visualisation treatment planning can be used in the quantitative calculation of tumour volume and the distance between the tumour and surrounding vital structures, as well as accurate simulation of 3D thermal fields and planning of the puncture pathway. 3D visualisation preoperative planning has been applied in liver thermal ablation [18,24,25]. On the basis of the characteristics and clinical application requirements of US-guided PMWA for larger RCC, we combined 3D visualisation treatment planning, US-guided PMWA, artificial ascites and a thermal monitoring system for larger RCC.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we presented a simulation environment for microwave thermal ablation (MWA) under the guidance of ultrasound developed in combination with our previous research [25][26][27][42][43][44]46] and other research [28][29][30][31][32][33][34][35][36][37][38][39][40][41]45]. Using these studies can save resources by avoiding 'reinventing the wheel', and can shorten the development cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers [33][34][35][36] have reported that pre-operative planning methods based on 3D image data are feasible for thermal ablation. Some computer 3D models of thermal therapy taking into account patient-specific anatomies have been developed for hyperthermia applications [37][38][39][40][41].…”
Section: Planning Navigation and Evaluationmentioning
confidence: 99%
“…Traditional trajectory planning methods presented in [2][3][4][5][6] tried to explore the practicability of computer aided design in puncture surgery planning. References [7][8][9][10][11][12][13][14] presented visualization methods to display puncture pathways in optimal views and better interactive methods to make it easier for surgeons to observe and adjust the planned puncture routes. References [15][16][17][18][19][20][21][22] focused on automatic or semiautomatic methods to output precisely optimized pathways.…”
Section: Introductionmentioning
confidence: 99%